Entropy in Human Systems: A Theoretical Model of Organizational Dysfunctions - Yoon, Byong-Man (Academy of Management Journal, 1968)
The article presents a dissertation abstract titled ?Entropy in Human Systems: A Theoretical Model of Organizational Dysfunctions,? by Byong-Man Yoon.